(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
With falling fertility rates in India, the fear of population explosion has receded; however, the challenges posed by the present population are enormous. This paper throws light on some recent trends in health and nutrition that are the adverse fallouts of a huge population. The recent fall in the ranks in Global Hunger Index of India from 83rd position in 2000 to 97th position among 118 countries in 2016 ring an alarming bell to the miserable condition of our present population. The paper has also discussed the looming dangers of a mismatch between rising young population and stagnant job growth as well as the far-fetched but approaching troubles of an ageing population.